Characterization of the Co-Flow Jet Effect as One of the Flow Control Devices - James Julian; Waridho Iskandar; Fitri Wahyuni; Ferdyanto; Nely Toding Bunga (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2022)
The computational study discusses the application of the co-flow jet technique as a fluid flow control device on the NACA 0015 airfoil. The numerical equation used is the RANS equation with the k-ε turbulence model. There are three variations of the mesh proposed in this paper. The first variation is a fine mesh with 100,000 elements. The second variation is a medium mesh with 50,000 elements. Meanwhile, the third variation is coarse mesh with 25,000 elements. Based on the mesh independence test results, the mesh with the lowest error value is the fine mesh. Co-flow jet is proven to control fluid flow on the upper side of NACA 0015. Co-flow jet can also improve the aerodynamic performance of NACA 0015 by increasing Cl and decreasing Cd. The increase in Cl was 114% and the decrease in Cd was 24%. The fluid flow separation on the upper side of the airfoil can also be handled well by the co-flow jet.